PKM Pembuatan Roti Pisang (Ropis Trinurisa) untuk Meningkatkan Pendapatan Masyarakat - Sri Utami; Nurjannah Nurjannah; Nur Arisah; Sitti Hajerah Hasyim; Mustari Mustari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
One of the Community Service activities that can increase the purchasing value of raw materials is bananas processed into Ropis Trinurisa (Banana Bread). Processing this product can increase community income with a home industry business or commonly called a home business in processing bananas into Ropis Trinurisa (Banana Bread). The methods used in this activity include lectures, questions and answers or discussions, and training and mentoring carried out in Tamalate District, Makassar City for 2 weeks. The results obtained are (1) Training on processing bananas into Ropis Trinurisa (Banana Bread) was responded well by the participants; (2) The high interest and motivation of the training participants greatly supports the transfer of knowledge and skills from the service providers to the training participants, so that the training materials provided can be absorbed by all; and (3) The training products for processing bananas into Ropis Trinurisa (Banana Bread) can be consumed daily and can be used as community entrepreneurial products.